A Rare Cause of Metabolic Acidosis: Fatal Transdermal Methanol Intoxication in an Infant. Issue 8 (August 2016) - Sahbudak Bal, Zumrut; Can, Fulya Kamit; Anil, Ayse Berna; Bal, Alkan; Anil, Murat; Gokalp, Gamze; Yavascan, Onder; Aksu, Nejat
Abstract : Abstract: Oral methanol intoxication is common, but dermal intoxication is rare. We report a previously healthy 19-month-old female infant admitted to the emergency department (ED) with vomiting and tonic-clonic seizure. On physical examination, she was comatose and presented signs of decompensated shock with Kussmaul breathing. Her left thigh was edematous, with purple coloration. Methanol intoxication was suspected due to high anion gap metabolic acidosis (pH, 6.89; HCO3, <3 meq/L) and exposure to spirit-soaked bandages (%96 methanol) for 24 hours and 3 days. The patient's serum methanol level was 20.4 mg/dL. She was treated with fomepizole and continuous venovenous hemodialysis (CVVHD) in the pediatric intensive care unit, and methanol levels decreased to 0 mg/dL after 12 hours. During follow-up, massive edema and subarachnoid hemorrhage in the occipital lobe were detected by computed tomography of the brain. The patient died after 7 days. Although methanol intoxication occurs predominantly in adults, it must be considered in children with high-anion gap metabolic acidosis. This case report demonstrates that fatal transdermal methanol intoxication can occur in children, and it is the second report in the English literature of transdermal methanol intoxication in an infant.